2010
DOI: 10.1007/s00464-009-0822-7
|View full text |Cite
|
Sign up to set email alerts
|

Is minimally invasive surgery beneficial in the management of esophageal cancer? A meta-analysis

Abstract: Minimally invasive esophagectomy is a safe alternative to the open technique. Patients undergoing MIE may benefit from shorter hospital stay, and lower respiratory complications and total morbidity compared with open esophagectomy. Multicenter, prospective large randomized controlled trials are required to confirm these findings in order to base practice on sound clinical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
179
2
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(215 citation statements)
references
References 26 publications
14
179
2
18
Order By: Relevance
“…To improve outcomes, minimally invasive esophagectomy (MIE) has been gradually accepted as a reliable surgical procedure for esophageal cancer (1,2). Although the procedure is technically demanding it has been suggested that MIE can be performed with low pulmonary complication rates (1,3) and comparable longterm oncological outcomes (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…To improve outcomes, minimally invasive esophagectomy (MIE) has been gradually accepted as a reliable surgical procedure for esophageal cancer (1,2). Although the procedure is technically demanding it has been suggested that MIE can be performed with low pulmonary complication rates (1,3) and comparable longterm oncological outcomes (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some of these metaanalyses demonstrate a trend to reduced mortality (7) and morbidity (15,(17)(18)(19) for patients who underwent an MIE compared to those who when operated with conventional open esophagectomy. Moreover, after MIE implementation we have seen a reduction in blood loss and shorter hospital stay (15,17,19).T h e s e f a v o r a b l e f i n d i n g s a s s o c i a t e d w i t h t h e implementation of MIE are also supported by the only to date published randomized controlled trial comparing open esophagectomy to MIE. This study showed a significantly reduced risk of pulmonary complications after MIE compared to open esophagectomy (34% vs. 12% respectively) (10).…”
mentioning
confidence: 99%
“…This has been shown in several meta-analysis (18)(19)(20) and a prospective randomized controlled trial (21).…”
Section: Diversity Of Approachesmentioning
confidence: 60%